2005
DOI: 10.1152/ajpregu.00594.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of angiotensinogen in astrocytes

Abstract: In the brain, angiotensinogen (AGT) is primarily expressed in astrocytes; brain ANG II derived from locally produced AGT has been shown to influence blood pressure. To better understand the molecular basis of AGT expression in the brain, we identified a human astrocytoma cell line, CCF-STTG1, that expresses endogenous AGT mRNA and produces AGT protein. Studies examining CCF-STTG1 cell AGT after N- and O-glycosidase suggest that AGT may not be posttranslationally modified by glycosylation in these cells as it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 47 publications
3
54
0
Order By: Relevance
“…The multiple forms of hAGT centering on 55 kDa reflect multiple glycosylated forms of the protein (5, 38). We previously reported that HepG2 cells also express multiple forms of hAGT protein, which become reduced to a single immunoreactive product after N-glycosidase treatment (34). Next, we demonstrated that equivalent levels of hAGT protein were detected in plasma of RA and RAC mice, confirming that removal of hAGT from the brain did not affect the ability of the liver to produce and secrete hAGT (Fig.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The multiple forms of hAGT centering on 55 kDa reflect multiple glycosylated forms of the protein (5, 38). We previously reported that HepG2 cells also express multiple forms of hAGT protein, which become reduced to a single immunoreactive product after N-glycosidase treatment (34). Next, we demonstrated that equivalent levels of hAGT protein were detected in plasma of RA and RAC mice, confirming that removal of hAGT from the brain did not affect the ability of the liver to produce and secrete hAGT (Fig.…”
Section: Resultssupporting
confidence: 74%
“…We previously reported astrocytic AGT mRNA in areas of the medulla, midbrain, hypothalamus, thalamus, and hippocampus (44). We also identified a human glioma cell line that expresses AGT endogenously (34). In contrast to glial AGT, neuronal expression of AGT is much more regionally restricted to the nucleus of the solitary tract (NTS), PVN, parabrachial nucleus, RVLM, mesencephalic trigeminal nucleus, and the subfornical organ (SFO) (14,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both methods show that AGT is widely expressed in astrocytes (32,131), and in those cells, was localized in the nucleus (122). Genetic deletion of glial-specific AGT lowers arterial pressure in double transgenic mice expressing both human renin and human AGT (121), and antisense inhibition of glial AGT in rats results is altered baroreflex regulation and increased exercise tolerance (43,119).…”
Section: Localization Of Ras Components Required For Ang II Productionmentioning
confidence: 99%
“…Although the direct demonstration of ANG II or ANG-(1-7) within the nuclear compartment of the kidney awaits further studies, identification of a renal cell line that expresses these RAS components may facilitate the elucidation of the processing pathways that contribute to the intracellular/nuclear generation of angiotensins. In this regard, Sigmund and colleagues (89) reported the presence of angiotensinogen in the nuclear compartment of glial cells and identified a putative NLS for the protein; however, the extent of processing of the precursor in the glial nuclei is not known. Both immunoreactive ANG-(1-7) and ANG II were detected in the perinuclear region of rat mesangial cells, in addition to the presence of intracellular ACE and ACE2 (9).…”
Section: Intracellular Formationmentioning
confidence: 99%